The Influence of Service Quality and Customer Value on Customer Loyalty - Rukayyah, Alitha; Yulianti, Sri Rahyuni Fifi Angriani Putri Naslia, (Pascasarjana STIE Amkop Makassar, 2024)
This study examines the influence of service quality and customer value on customer loyalty. In today's competitive market, understanding the factors that drive customer loyalty is crucial for businesses aiming to retain customers and achieve long-term success. The research explores the relationship between service quality, customer value, and customer loyalty, hypothesizing that both service quality and customer value significantly impact loyalty. Data were collected through surveys from a sample of customers across various industries, and structural equation modeling (SEM) was employed to analyze the relationships. The findings reveal that both service quality and customer value have a positive and significant effect on customer loyalty, with customer value acting as a partial mediator between service quality and loyalty. The study concludes that businesses should prioritize delivering high-quality services and creating superior customer value to foster customer loyalty. Practical implications and recommendations for managers are discussed, emphasizing the importance of aligning service delivery with customer expectations and perceived value. Keywords: Service Quality, Customer Value, Customer Loyalty, Structural Equation Modeling (SEM), Customer Retention.